LncRNA TINCR is downregulated in diabetic cardiomyopathy and relates to cardiomyocyte apoptosis. (2nd November 2018) - Chen, Yongheng; Tan, Shan; Liu, Mei; Li, Jianming
Abstract: Objective. LncRNA TINCR has been reported to be involved in cardiac hypertrophy, while its involvement in diabetic cardiomyopathy is unknown. Materials and methods . In this study, myocardial biopsy and serum collected from patients with diabetic cardiomyopathy, diabetic patients without cardiopathy and healthy controls, and the expression of TINCR in those tissues was detected by quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR). ROC curve analysis was performed to evaluate the diagnostic value of TINCR expression for diabetic cardiomyopathy. Human cardiomyocyte cells (Cat# 12440053, Thermo Fisher Scientific) were treated with high glucose, and the expression of TINCR was detected by qRT-PCR. TINCR expression was transfected into cardiomyocyte cells and cell apoptosis under high glucose treated was detected by cell apoptosis assay. Results . We found that TINCR expression level in myocardial biopsy and serum was significantly lower in patients with diabetic cardiomyopathy than in diabetic patients without cardiopathy and healthy controls, while no significant differences were found between diabetic patients without cardiopathy and healthy controls. TINCR expression level can be used to effective diagnose diabetic cardiomyopathy. High glucose treatment showed no significant effects on the expression of TINCR in human cardiomyocyte cells, and TINCR overexpression inhibited apoptosis of cardiomyocytes under high glucose treatment. Conclusion . Therefore, we conclude that lncRNA TINCR is downregulated in diabetic cardiomyopathy and it can inhibit cardiomyocyte apoptosis.